2018
DOI: 10.1016/j.jprot.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

RAGE-induced changes in the proteome of alveolar epithelial cells

Abstract: In the present study, we undertook the first proteomic evaluation of RAGE-dependent processes in alveolar epithelial cells. The alveolar epithelium is a primary target during acute lung injury, and our data support a role for RAGE in gene transcription, protein transport, and response to stimuli. More over our data suggest that RAGE is a critical driver of redox regulation in the alveolar epithelium. The conclusions of the present work assist to unravel the molecular events that underlie the function of RAGE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Previous studies have revealed that ROS play a role in the pathogenesis of lung in ammation, the generation of mitochondrial ROS is crucial for NLRP3 in ammasome activation, leading to the release of IL-1β [21]. Here, our in vitro data demonstrated that ROS promotes in ammation in alveolar epithelial cells, alveolar epithelial injury leads to the impairment of air exchange function and, more importantly, the secretion of IL-1β [22]. We also found that treatment of LPS induced ROS generation in HPAEpiC, leading to activation of NLRP3 in ammasome, and this effect was alleviated by NAC, an antioxidant.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have revealed that ROS play a role in the pathogenesis of lung in ammation, the generation of mitochondrial ROS is crucial for NLRP3 in ammasome activation, leading to the release of IL-1β [21]. Here, our in vitro data demonstrated that ROS promotes in ammation in alveolar epithelial cells, alveolar epithelial injury leads to the impairment of air exchange function and, more importantly, the secretion of IL-1β [22]. We also found that treatment of LPS induced ROS generation in HPAEpiC, leading to activation of NLRP3 in ammasome, and this effect was alleviated by NAC, an antioxidant.…”
Section: Discussionsupporting
confidence: 61%
“…Our understanding of the role of RAGE is largely limited to studies in diabetes and Alzheimer’s disease, and recent work from our laboratory has identified that RAGE is a crucial protein involved in maintenance of the alveolar epithelium (Downs et al, 2018). Indeed, RAGE is constitutively and abundantly expressed in the lung, suggesting that it may have important physiological functions (Brett et al, 1993; Downs et al, 2015; Downs et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Cells are lysed with RIPA buffer (CST# 9806) in presence of Protease/Phosphatase Inhibitor Cocktail (CST# 5872) followed by acetone precipitation of proteins and handed over to core facility for LC-MS/MS. Proteins identification by LC-MS/MS were performed following core facility’s standard optimized protocol [ 24 ]. Tandem mass spectra were searched against the human fasta protein database from UniprotKB downloaded on October 06, 2015 (69,961 entries), to which additional common contaminant proteins (eg., trypsin; obtained at ftp://ftp.thegpm.org/fasta/cRAP ) were appended.…”
Section: Methodsmentioning
confidence: 99%